Examen crítico de la relación entre empleo y educación en el contexto de la globalización. - Barrigüete Garrido, L. Miguel (Revista Complutense de Educación, 2006)
The globalization with its man reduction to the dimension of an "economic man" have intensified the poverty, the unemployment and the precarious employment, which, in our industrial society, means the threshold of the poverty. These are, among others, the main signs of the current pattern of economic development that is focused in the market logic. Therefore, the workers have been reduced to "merchandise-men" and, if their rights do not represent more than their mercantile relation, we could wonder: what is the work? And what is the meaning of their work? On the other side, the relations between the education and the employment always seem to be one of the main worries of the educational planning. This way, in many economists' opinion, the solution to unemployment would consist in the enlargement of the capital formation first and in the investment in education later. Nevertheless, certain evidences allow us to think that the increase of the capital by worker and the high rates of economic growth have not brought the descent of the unemployment rates, and the higher instruction level by worker do not seem to have had other effect on the unemployment than the increase of the average instruction level of the unemployed.